A minimalistic approach to develop new anti-apicomplexa polyamines analogs - Panozzo Zenere, Esteban Andrés (2018)
The development of new chemical entities against the major diseases caused by parasites is highly desired. A library of thirty diamines analogs following a minimalist approach and supported by chemoinformatics tools have been prepared and evaluated against apicomplexan parasites. Different member of the series of N,N′-disubstituted aliphatic diamines shown in vitro activities at submicromolar concentrations and high levels of selectivity against Toxoplasma gondii and in chloroquine-sensitive and resistant-strains of Plasmodium falciparum. In order to demonstrate the importance of the secondary amines, ten N,N,N′,N′-tetrasubstituted aliphatic diamines derivatives were synthesized being considerably less active than their disubstituted counterpart. Theoretical studies were performed to establish the electronic factors that govern the activity of the compounds.